2018
DOI: 10.1353/eco.2018.0008
|View full text |Cite
|
Sign up to set email alerts
|

Homicides and the Age of Criminal Responsibility: A Density Discontinuity Approach

Abstract: We employ a density discontinuity design to evaluate the deterrence effect of more severe punishments around the legal age of criminal responsibility in Brazil. Motivated by the criminology literature, we propose a novel proxy based on the inherent risk underlying criminal activities. Using violent death rates as a proxy for an individual's involvement in violent crime, we find no discernible deterrence effects. We additionally study arrest data from the country's third most populous state, Rio de Janeiro, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(58 reference statements)
1
1
1
2
Order By: Relevance
“…Therefore, it can be concluded that, in the particular set up of Rio de Janeiro, increasing punishment severity would reduce these crimes and would reduce engagement in criminal activities. These results differ from studies that used similar methodologies, such as Lee and McCrary (2017) and Costa et al (2018). However, they are in agreement with those of other authors such as Kessler and Levitt (1999), Helland and Tabarrok (2007), Drago et al (2007) and Loeffler and Grunwald (2015), who also used robust methods (i.e., based on natural experiments and quasi-experiments).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, it can be concluded that, in the particular set up of Rio de Janeiro, increasing punishment severity would reduce these crimes and would reduce engagement in criminal activities. These results differ from studies that used similar methodologies, such as Lee and McCrary (2017) and Costa et al (2018). However, they are in agreement with those of other authors such as Kessler and Levitt (1999), Helland and Tabarrok (2007), Drago et al (2007) and Loeffler and Grunwald (2015), who also used robust methods (i.e., based on natural experiments and quasi-experiments).…”
Section: Discussionsupporting
confidence: 80%
“…One possible explanation for the differences in magnitude between this study and that of Lee and McCrary (2017) is that both Lee and McCrary (2017) and Costa et al (2018) grouped violent crimes. This empirical strategy may produce misleading conclusions about the deterrence effects of increasing punishment severity.…”
Section: All Observationscontrasting
confidence: 61%
“…Em Carneiro, Soares e Ulyssea (2015) os autores exploram a relação entre o choque de liberalização comercial brasileira da década de 1990 e o crime. Além desse, Costa et al (2016) exploram uma descontinuidade de densidade para tentar avaliar mudanças por se atingir a maioridade penal no comportamento criminoso individual. Ambos trabalhos exploram o fato de que homícidios causados por mortes violentas podem servir de boas proxies da atividade criminal.…”
Section: Economia Do Crimeunclassified
“…Além disso, a literatura de Economia Comportamental analisada pela ótica de esportes é algo pouco explorada, então o trabalho aqui visa contribuir com mais resultados empíricos. Por fim, o tema de criminalidade no Brasil é algo bastante relevante e com alguns trabalhos de grande importância (SOARES, 2004;CERQUEIRA, 2014;CARNEIRO;ULYSSEA, 2015;COSTA et al, 2016) e entende-se que existe certa importância para enriquecer o debate.…”
unclassified
“…This first examination suggests that both groups follow the same pattern of mortality due to homicides, with a sharp dip in the rates from 2007 to 2013. 3.3.1 We use the same ICD-10 codes from Costa et al (2018), which account for misreporting and undereporting as suggested by Cerqueira (2013). Figura A1 -Homicide rates in Pernambuco by different age groups…”
Section: Data and Summary Statisticsmentioning
confidence: 99%